ANALISIS KINERJA KEUANGAN DILIHAT DARI CURRENT RATIO, DEBT TO EQUITY RATIO, DAN TOTAL ASSET TURNOVER PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR FARMASI - Hartini Hartini; Nini Hardianti (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
Financial performance is a description of a company's financial condition related to its financial aspects. This study aimed to determine and analyze partially or simultaneously the effect of the variables Current Ratio (CR), Debt-to-EquityRatio (DER) and Total Assets Turnover (TATO) on Return on Assets (ROA). The population in this study were pharmaceutical companies listed on the Indonesia Stock Exchange from 2016-2020, which were then selected using a purposive sampling technique, resulting in a sample of seven companies. The analytical method used in this study was panel data regression analysis with the requirements test, specifically the classical assumption test utilizing the EViews 9 program. The results of this study indicate that the Current Ratio (CR) has a significant effect on Return on Assets (ROA), the Debt-to-EquityRatio (DER) has no effect on Return on Assets (ROA), and Total Assets Turnover (TATO) has a significant effect on Return on Assets (ROA). This study also shows that the Current Ratio, Debt-to-Equity Ratio, and Total Assets Turnover have a simultaneous effect on Return on Assets (ROA).